2022
DOI: 10.3390/plants11060743
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid and 24-Epibrassinolide Improve the Drought Stress Resilience and Productivity of Banana Plants

Abstract: Plant growth, development, and productivity are adversely affected under drought conditions. Previous findings indicated that 5-aminolevulinic acid (ALA) and 24-epibrassinolide (EBL) play an important role in the plant response to adverse environmental conditions. This study demonstrated the role of ALA and EBL on oxidative stress and photosynthetic capacity of drought-stressed ‘Williams’ banana grown under the Egyptian semi-arid conditions. Exogenous application of either ALA or EBL at concentrations of 15, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 146 publications
1
12
0
3
Order By: Relevance
“…Silicon nanoparticles have been found to play an important role in a plant's ability to overcome the adverse effects of environmental stresses [12,[69][70][71][72]. Several researchers have reported the ability of nSi to improve a plant's resistance to drought stress [29,73].…”
Section: Discussionmentioning
confidence: 99%
“…Silicon nanoparticles have been found to play an important role in a plant's ability to overcome the adverse effects of environmental stresses [12,[69][70][71][72]. Several researchers have reported the ability of nSi to improve a plant's resistance to drought stress [29,73].…”
Section: Discussionmentioning
confidence: 99%
“…Brassinosteroids (BR) are a major class of growth-promoting hormones that regulate plant growth and development in many aspects of plant life, such as cell elongation and responses to various environmental stresses, including drought stress [ 17 , 18 ]. Several studies have shown that BR application confers drought tolerance via higher antioxidant enzyme activities such as SOD, POD, and CAT, along with a higher accumulation of proline, and consequently lowered the ROS production and MDA content [ 19 , 20 , 21 ]. 2,4-epibrassinolide (EBR) application proved as an effective stress ameliorating approach.…”
Section: Introductionmentioning
confidence: 99%
“…Algunas de las razones de realizar la aplicación de BR en frutales es su función en la disminución del impacto de las condiciones agroclimáticas adversas sobre la fotosíntesis (Figura 1). Los BR aumentan los contenidos de enzimas antioxidantes y aportan a la estabilidad en el contenido total de clorofilas (Xia et al, 2022;Castañeda et al, 2022;Helaly et al, 2022;Karlidag, 2011). Se ha reportado que la aplicación exógena de BR y análogos (24-Epibrassinolide -EBR) en frutales bajo estrés por déficit hídrico, aumenta la actividad de enzimas antioxidantes como Ascorbato Peroxidasa (APX), Glutatión Peroxidasa (GR), Catalasa (CAT), Superóxido Dismutasa (SOD) y Peroxidasa (POD), lo que genera una marcada reducción del daño por la producción de ROS a causa de la disminución del contenido de malondialdehido (MDA) y peróxido de hidrógeno (H2O2) como se ha reportado en plantas de lulo (Castañeda et al, 2022), banano (Helaly et al, 2022), durazno (Wang et al, 2019a), vid (Wang et al, 2019b) y kiwi (Xia et al, 2022).…”
Section: Influencia De Brasinoesteroides En El Metabolismo De Frutale...unclassified
“…Los BR aumentan los contenidos de enzimas antioxidantes y aportan a la estabilidad en el contenido total de clorofilas (Xia et al, 2022;Castañeda et al, 2022;Helaly et al, 2022;Karlidag, 2011). Se ha reportado que la aplicación exógena de BR y análogos (24-Epibrassinolide -EBR) en frutales bajo estrés por déficit hídrico, aumenta la actividad de enzimas antioxidantes como Ascorbato Peroxidasa (APX), Glutatión Peroxidasa (GR), Catalasa (CAT), Superóxido Dismutasa (SOD) y Peroxidasa (POD), lo que genera una marcada reducción del daño por la producción de ROS a causa de la disminución del contenido de malondialdehido (MDA) y peróxido de hidrógeno (H2O2) como se ha reportado en plantas de lulo (Castañeda et al, 2022), banano (Helaly et al, 2022), durazno (Wang et al, 2019a), vid (Wang et al, 2019b) y kiwi (Xia et al, 2022). En experimentos realizados en manzano (Malus domestica) sometidos a déficit hídrico, se identificó que la aplicación foliar de brasinoesteroides aumentó los contenidos de prolina en la hoja, situación que le permite una mejor respuesta al estrés abiótico (Kumari y Thakur, 2019a,b;Kumari et al, 2020).…”
Section: Influencia De Brasinoesteroides En El Metabolismo De Frutale...unclassified
See 1 more Smart Citation